Policy Challenges and Political Responses Public Choice Perspectives on the Post-9/11 World - Shughart II, William F.; Tollison, Robert D. (Springer US : Imprint: Springer, 2005)
In Policy Challenges and Political Responses, leading public choice scholars confront the most significant problems facing democratic societies at the dawn of the 21st century. Ranging widely across the policy spectrum, this authoritative volume demonstrates the vibrancy and continuing relevance of the public choice research program by applying its ideas and methods to constitution-making in the European Union, terrorism, the growth of government, political campaign finance, vote-counting technologies, participatory democracy, corporate governance, school choice, and tort reform. Essays assessing the present state of the social contract and the enduring tensions between capitalism, socialism, and democracy broaden the book's perspective. The distinguished list of contributors includes James Buchanan, Charles Rowley, Dennis Mueller, Todd Sandler, Randall Holcombe, Michael Munger, Thomas Stratmann, Harold Mulherin, Lawrence Kenny, and Paul Rubin. Edited by two of the editors of the journal Public Choice and as fresh as today's headlines, this volume positions the public choice literature in the context of current events and points its research agenda in new directions. It is a unique and indispensable collection of value to economists, political scientists, political philosophers, and public policymakers.